Fcer1g and St3gal1: Macrophage-associated angiogenesis biomarkers and therapeutic targets in sepsis-induced acute lung injury - Lu Liu; Peiyao Luo; Man Wang; Shihuan Yu; Jinling Xiao (PLoS ONE, 2026)
Background Acute lung injury (ALI) involves the release of growth factors and inflammatory mediators from damaged pulmonary tissues, fostering endothelial cell proliferation, migration, and vascular lumen formation, thereby driving pathological angiogenesis. Macrophages contribute to angiogenesis and vascular homeostasis, but their dysregulation in pathological states worsens vascular dysfunction. This study aims to identify macrophage-associated angiogenesis-related genes as novel diagnostic biomarkers and therapeutic targets for sepsis-associated ALI (SALI). Methods Transcriptomic datasets from the GEO database were analyzed using differential expression profiling and weighted gene co-expression network analysis (WGCNA) to identify candidate genes. These candidates were compared with macrophage- and angiogenesis-related gene sets from GENECARDS for functional prioritization. Three machine learning algorithms (LASSO regression, random forest, and SVM) were employed to refine predictive biomarkers, followed by immune infiltration analysis (via CIBERSORT) to assess correlations with immune subsets. Single-cell RNA sequencing and RT-PCR were used for spatial validation of gene expression. Results Two macrophage-associated angiogenesis-related genes, Fcer1g (FCER1G) and St3gal1 (ST3GAL1), were identified as key biomarkers. Both genes showed significant upregulation in the training cohort (p < 0.001) and independent validation sets (p < 0.05), with robust diagnostic accuracy (AUC > 0.85). Immune correlation analysis indicated strong positive associations with macrophage infiltration (p < 0.01), particularly M2-polarized subsets. scRNA-seq confirmed their predominant expression in macrophage clusters, with increased activity in SALI tissues (log2FC > 2.0, p < 0.001). Conclusions In mouse in vivo studies, Fcer1g and St3gal1 were shown to precisely mediate intricate macrophage-endothelial cell interactions via glycoimmune signaling pathways at the molecular level. This interaction finely modulates endothelial cell activation and drives angiogenic remodeling, critically impacting SALI progression. Given the physiological and pathological parallels between mice and humans, our findings offer a theoretical underpinning for subsequent human – oriented research. Moving forward, efforts should focus on verifying the expression patterns, action mechanisms, and diagnostic/therapeutic potential of these genes in relation to human SALI – associated signatures.